2011
DOI: 10.1074/jbc.m110.115931
|View full text |Cite
|
Sign up to set email alerts
|

Small Ubiquitin-related Modifier (SUMO)-1 Promotes Glycolysis in Hypoxia

Abstract: Under conditions of hypoxia, most eukaryotic cells undergo a shift in metabolic strategy, which involves increased flux through the glycolytic pathway. Although this is critical for bioenergetic homeostasis, the underlying mechanisms have remained incompletely understood. Here, we report that the induction of hypoxia-induced glycolysis is retained in cells when gene transcription or protein synthesis are inhibited suggesting the involvement of additional post-translational mechanisms. Post-translational protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 39 publications
7
63
0
2
Order By: Relevance
“…Hypoxia-induced transcription of SUMO1 or R WD-containing SUM Oylation enhancer (RSUME) might explain the global effects on SUMOylation by directly targeting the conjugation machinery (Comerford et al , 2003 ;Shao et al , 2004 ;Carbia -Nagashima et al, 2007 ), while regulation of specific SUMO E3 ligases, such as PIAS4, might account for more restricted effects . Furthermore, SUMO1 overexpression has been related with an increase in glycolysis and glucose uptake (Agbor et al , 2011 ). It has been proposed that SUMO could play a role in the metabolic switch to glycolysis, contributing to the cellular adaptation to hypoxia, which is consistent with the fact that GLUT-1 and GLUT-4 are substrates for SUMO (Giorgino et al , 2000 ).…”
Section: Sumoylation and The Adaptation To Hypoxiasupporting
confidence: 57%
“…Hypoxia-induced transcription of SUMO1 or R WD-containing SUM Oylation enhancer (RSUME) might explain the global effects on SUMOylation by directly targeting the conjugation machinery (Comerford et al , 2003 ;Shao et al , 2004 ;Carbia -Nagashima et al, 2007 ), while regulation of specific SUMO E3 ligases, such as PIAS4, might account for more restricted effects . Furthermore, SUMO1 overexpression has been related with an increase in glycolysis and glucose uptake (Agbor et al , 2011 ). It has been proposed that SUMO could play a role in the metabolic switch to glycolysis, contributing to the cellular adaptation to hypoxia, which is consistent with the fact that GLUT-1 and GLUT-4 are substrates for SUMO (Giorgino et al , 2000 ).…”
Section: Sumoylation and The Adaptation To Hypoxiasupporting
confidence: 57%
“…In this study, we showed that EAF2 modulated the induction of several cellular glucose metabolismrelated genes downstream of HIF-1␣, such as SLC2A (Glut-1), PDK-1, and LDHA. Thus, we investigated whether EAF2 can also affect cellular glucose metabolism by measuring cellular glucose uptake in the presence or absence of EAF2 with a Biovision glucose uptake assay kit, as employed by previous investigators, following the protocol provided by the manufacturer (15,35,36). Under hypoxic conditions, EAF2…”
Section: Resultsmentioning
confidence: 99%
“…Whole-cell, nuclear and cytosolic extracts were generated in either normoxia or hypoxia according to previously published protocols [30,31]. Protein concentration was quantified using a Bradford assay, and samples were normalised accordingly.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Protein concentration was quantified using a Bradford assay, and samples were normalised accordingly. Samples were separated by SDS-PAGE and immunoblotted as described previously [30,31] using the following primary Abs and dilutions: HIF-1# (1:250; BD Pharmingen), "-actin (1:10,000; Sigma) and TATA box binding protein (TBP; 1:2500; Abcam).…”
Section: Western Blot Analysismentioning
confidence: 99%